Objective and Subjective Measures of Children's Engagement With Auditory Narratives. - Robinson, Sophia M. H.; Platkin, Rafaela; Bobbitt, Sarah; Van Hedger, Stephen; Butler, Blake E. (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Listening engagement describes the extent to which an individual recruits cognitive resources for a listening task, potentially contributing to the experience of listening effort--the subjective experience of exerting cognitive resources to process sounds. This study explored the use of spoken narrative stimuli to assess two different measures of listening engagement in children and objectively assess their engagement in stories. Method: Seventy children (31 female; M = 10.3 years) between the ages of 9-12 years listened to two engaging stories containing different child-preferred themes and a non-engaging control story lacking these themes. Engagement was measured using two methods: a self-report measure (a version of the Story World Absorption Scale) and a performance-based measure (a speeded directional judgment task) presented concurrently with the stories. Results: Stories with child-preferred themes were rated as more engaging than the control story via self-report. Moreover, secondary task reaction times were significantly slower while listening to engaging stories than the control story, suggesting that engaging stories placed higher demands on cognitive resources. Intersubject correlation analyses revealed that reaction times across the duration of engaging stories were more consistent than across the control story, suggesting that reaction times reflected a shared response to narrative content. Conclusion: Together, these results suggest that children's engagement with auditory narratives can be measured objectively and that engagement varies across stories in a manner that is qualitatively similar to adults.